2011
DOI: 10.1182/blood-2010-07-294520
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses to transgene and retroviral vector in patients treated with ex vivo–engineered T cells

Abstract: Adoptive transfer of immune effector cells that are gene modified by retroviral transduction to express tumor-specific receptors constitutes an attractive approach to treat cancer. In patients with metastatic renal cell carcinoma, we performed a study with autologous T cells genetically retargeted with a chimeric antibody receptor (CAR) directed toward carbonic anhydrase IX (CAIX), an antigen highly expressed in renal cell carcinoma. In the majority of patients, we observed distinct humoral and/or cellular ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
308
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(314 citation statements)
references
References 48 publications
2
308
0
2
Order By: Relevance
“…This contrasts with other recent CAR studies that found antitransgene immune responses directed against the NeoR gene or scFv epitopes. 45,46 This may be partially explained by the low level of transgene expression observed in our study, but it is probably the result of the impaired immunity of lymphoma patients that mitigates against rejection of genetically modified T cells. The small number of patients treated on this trial makes it difficult to draw definitive conclusions about the immunogenicity of our CAR protein, but it is worth striving to minimize potential immunogenicity in designing future CARs by using humanized Abs, minimizing junctional regions, and avoiding xenogeneic genes, such as those encoding for antibiotic resistance.…”
Section: Discussionmentioning
confidence: 66%
“…This contrasts with other recent CAR studies that found antitransgene immune responses directed against the NeoR gene or scFv epitopes. 45,46 This may be partially explained by the low level of transgene expression observed in our study, but it is probably the result of the impaired immunity of lymphoma patients that mitigates against rejection of genetically modified T cells. The small number of patients treated on this trial makes it difficult to draw definitive conclusions about the immunogenicity of our CAR protein, but it is worth striving to minimize potential immunogenicity in designing future CARs by using humanized Abs, minimizing junctional regions, and avoiding xenogeneic genes, such as those encoding for antibiotic resistance.…”
Section: Discussionmentioning
confidence: 66%
“…The majority of CARs utilized in current clinical trials contain scFv fragments derived from murine monoclonal antibodies, which may lead to the induction of humoral immune responses in the host as a reaction to the xenogeneic proteins. For instance, the development of anti-CAR immune responses in metastatic renal cell cancer patients treated with a murine anti-CAIX CAR was analyzed in detail, and it was postulated that T cell function and persistence may have been negatively impacted by this effect (Lamers et al, 2011). Most concerning, it was recently reported that repeated administration of murine CAR-engineered T cells led to development of antimouse antibody responses, associated with anaphylaxis and cardiac arrest in one subject (Maus et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These murine components are often immunogenic and able to elicit both cellular and humoral host 35 Cellular immune responses to either the murine components or the junction components of CARs may play a role in limiting the long-term persistence of CAR T cells in some patients and may decrease overall CAR T cell efficacy. 36 Although many drugs and immunotherapies can be administered recursively, immune responses to foreign proteins can also result in allergic sensitization.…”
Section: Allergic Reactions To Carsmentioning
confidence: 99%